2009
DOI: 10.1111/j.1751-2980.2008.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiological analysis of the relationship between pancreatic cancer and diabetes mellitus: Data from a single institution in China

Abstract: OBJECTIVE:  To investigate the relationship between pancreatic cancer (PC) and diabetes mellitus. METHODS:  All PC patients diagnosed and treated at Zhongshan hospital from January 1991 to December 2007 were retrospectively analyzed. During this period, 770 non‐digestive tract, non‐neoplastic and non‐hormone‐related patients matched for sex and age were collected as controls. The incidence of diabetes mellitus between the two groups was compared. RESULTS:  Between the PC group and the control group, sex and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
3
8
1
Order By: Relevance
“…The percentage of patients with jaundice and serum TBIL levels was significantly higher in PDA patients with diabetes than those without (40.0 vs. 23.1%; 8.54 ± 14.88 vs. 4.16 ± 6.12; P \ 0.05). However, there was no significant difference in tumor size, location, differentiation, TNM stage, hepatic metastasis between these two groups, which was consistent with the former reports (Kuang et al 2009;Pannala et al 2008). Similar to the results of Hb and ALT, there were no statistically significant differences in mean serum CEA and CA 19-9 level between PDA patients with or without diabetes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The percentage of patients with jaundice and serum TBIL levels was significantly higher in PDA patients with diabetes than those without (40.0 vs. 23.1%; 8.54 ± 14.88 vs. 4.16 ± 6.12; P \ 0.05). However, there was no significant difference in tumor size, location, differentiation, TNM stage, hepatic metastasis between these two groups, which was consistent with the former reports (Kuang et al 2009;Pannala et al 2008). Similar to the results of Hb and ALT, there were no statistically significant differences in mean serum CEA and CA 19-9 level between PDA patients with or without diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that 25.6% of PDA patients met the diagnostic standard for diabetes, which was in line with the findings (22.8%) reported by Gullo et al (1994). Another data from a single institution in China demonstrated the incidence of diabetes was 34.63% (169/488) in pancreatic cancer (Kuang et al 2009). Nevertheless, the reported percentage of diabetes in pancreatic cancer varies greatly according to the methods and criteria used for the diagnosis of diabetes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An exception is prostate cancer, for which diabetes appears protective [83, 84]. Studies demonstrating this association have been conducted across several different countries, including Italy [9, 26, 42], Sweden [3], Japan [35, 37, 40, 41, 61, 65], Scotland [66], the USA [7, 13, 14, 17, 20, 28, 36, 47, 48, 50, 55, 7880], the UK [81], Turkey [11], China [8, 39], and New Zealand [24]. Information sources used to ascertain DM and cancer diagnoses in these international studies are quite diverse and include self-report in surveys and questionnaires; hospital discharge and admission records; well-defined long-term national longitudinal cohorts; documentation of fasting or postprandial glucose tests; medical records; and for cancer diagnosis, use of histological evaluation and cancer registry or death registry [380].…”
Section: Cancer Riskmentioning
confidence: 99%
“…Some epidemiological studies have excluded the possibility that long-standing DM is a risk factor for PC [96][97][98][99][100][101][102][103][104][105][106][107][108] , whereas others have found the otherwise [109][110][111][112][113][114][115][116] .…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 99%